The environmental impact of mining activities in Europe: a comprehensive analysis - Edmond Hoxha; Lyudmyla Symochko; Maria Nazare Coelho Pinheiro (EQA)
Mining activities have emerged as major contributors to environmental damage. This paper offers an analyse of the actual situation of environmental damages caused by mining activities in Europe. Alarmingly, pollution from mining activities in the European Union is increasing. Surface and underground mining have detrimental effects on air and water quality, land degradation, waste disposal, noise pollution, deforestation and loss of biodiversity, endangered species, microbiota, economy, and health. Moreover, the risk of dam destruction because of climate change is increased. Globally this fact ranked Europe in second place in terms of dangerousness. The situation of protected species is critical and their status remains poor. The rehabilitation cost is exorbitant, and enforcement of regulations is lacking. It is evident that, due to economic demand for metals, mining will play a central role in EU's future despite the growing emphasis on green initiatives and transition. Unfortunately, public awareness regarding environmental impact of mining activities is insufficient, and their voices are often disregarded. In order to reduce the negative impact of mining on the environment, economy and public health, it is necessary to take urgent political and technical measures. This paper aims to present a comprehensive overview and offer suggestions for future actions.